Implementation of Problem Based Learning Strategy in Social Studies Subjects in Junior High Schools - Ahmad Zamroni; Amrin, Amrin (Council: Education Journal of Social Studies, 2025)
Problem-based learning strategies emphasize learning experiences, so that students can reconstruct their knowledge based on problems. The objectives of this study; 1) describe the planning of social studies learning using the PBL strategy; 2) Describe the implementation of social studies learning using the PBL strategy; 3) Identify the evaluation of the implementation of social studies learning using the PBL strategy. The research method used is qualitative which produces descriptive data in the form of written or spoken words. The purpose of descriptive research is to create descriptions, pictures or paintings systematically, and produce accurate pictures and knowledge that can be used in describing a symptom or phenomenon that occurs in the field. The results of the study of the implementation of the PBL learning strategy at SMPN 1 Tlogosari using learning media in the form of social studies subject videos, are considered to be very helpful for students actively in developing critical thinking, and reconstructing new knowledge from direct learning experiences examining problems. These results also show that the PBL strategy has close relevance to social studies learning because it focuses on social problems, as a basis for contextual knowledge construction